Necropolis - Horowitz, Anthony, 1955- (London Walker Books Ltd., 2013)
Evil has been unleashed on the world and only five children - with special powers - can save it. Matt and the other three desperately need to find Scar, the final gatekeeper, who has been trapped in Hong Kong, where puddles of water turn into puddles of blood, where ghosts, demons and hideous creatures stalk the streets. Matt has no choice but to follow her. Now, both imprisoned, their only hope of survival is to reach a secret door in the Man Ho temple. But even if Scar can find her psychic power, it may already be too late.
Formerly CIP.
Originally published: 2008.
Keywords: Freeman, Matt (Fictitious character) -- Fiction; Hong Kong (China) -- Fiction; Paranormal fiction; Young adult fiction